Reconceptualising quality models to achieve innovation objectives. (27th December 2006) - McAdam, Rodney; Mitchell, Neil
Increased competition has led to organisations facing the challenge of implementing quality management to achieve best practice, while at the same time having to address the need for innovation management to develop new products, services and processes. The aim of this paper is to explore the relationship between quality management and innovation management from a perspective that recognises the full contribution of quality management to academia and praxis. The research question in the paper is, how can organisations use their existing quality models to achieve their innovation management objectives? A multiple- and segmented-case analysis is used to show, first, how organisations have applied quality models based on quality objectives and, second, how the same organisations have used these quality models to achieve innovation objectives. The findings show that the concepts of a quality-innovation continuum and that of quality as a preceding foundation for innovation can help organisations reconceptualise and reapply their quality models to achieve innovation objectives.